Inhibition of Connexin 43 and Phosphorylated NR2B in Spinal Astrocytes Attenuates Bone Cancer Pain in Mice - Yang, Hui; Yan, Hui; Li, Xin; Liu, Jing; Cao, Shousong; Huang, Baisheng; Huang, Dong; Wu, Lixiang (Frontiers in Cellular Neuroscience, 2018)
Bone cancer pain (BCP) is common in patients with advanced cancers when the tumors are metastasized to bone. The limited understanding of the complex pathogenesis of BCP leads to the poor effectiveness of clinical treatment. Previous studies have shown that astrocyte-specific connexin (Cx) 43, a forming protein of gap junction (GJ) and hemichannel, and N-methyl-D-aspartate receptors (NMDARs), especially the phosphorylated NR2B (p-NR2B) subunit are involved in BCP. However, the relationship between Cx43 and p-NR2B in BCP remains unclear. In the present study, we investigated the expressions of Cx43, glial fibrillary acidic protein (GFAP, a marker of astrocytes), and p-NR2B in the spinal dorsal horn (SDH) in a mouse model of BCP established by intra-femural inoculation of Lewis lung carcinoma (LLC) cells via intrathecal injection of the GJ/hemichannel blocker carbenoxolone (CARB) and the NMDAR antagonist MK801, respectively. We found that the characters of BCP were mimicked by intra-femural inoculation of LLC cells in mice, and the expressions of Cx43, GFAP and p-NR2B in BCP mice were remarkably increased in a time-dependent manner from day 7 to day 21 after cell inoculation with a gradual aggravate in spontaneous pain and mechanical allodynia. Furthermore, Cx43 was predominantly expressed in the spinal astrocytes. Both CARB and MK801 inhibited the expressions of Cx43, GFAP and p-NR2B with attenuated pain hypersensitivity in BCP mice. In addition, Cx43 was co-localized with p-NR2B in the SDH, which further evidenced the presence of functional NR2B in the spinal astrocytes in BCP mice. Our findings demonstrate that inhibition of Cx43 and p-NR2B in spinal astrocytes could attenuate BCP in mice and Cx43 and p-NR2B in the astrocytes of the SDH may play an important role via their combination action in the development and maintenance of BCP in mice. These results may provide a potential therapeutic target in the prevention and/or treatment of BCP.